Molecular insights on the evolution of the lateral and head lantern luciferases and bioluminescence colors in Mastinocerini railroad-worms (Coleoptera: Phengodidae) - Arnoldi, Frederico G. C. [UNESP]; da Silva Neto, Antonio Joaquim [UNESP]; Viviani, Vadim R. (Royal Soc Chemistry, 2010)
Among bioluminescent beetles of Elateroidea superfamily, railroad-worms (Phengodidae) produce the widest range of colors, from green to red, using the same luciferin-luciferase system. Members of the Mastinocerini tribe display additional unique cephalic organs that emit red-shifted light, with Phrixothrix railroad-worms being the most dramatic cases with head lanterns emitting red light. Although the luciferases from the head lanterns of Phrixothrix hirtus and from the lateral lanterns of P. vivianii were previously cloned, the luciferases from both lanterns of the same species were not cloned yet. Therefore the origin and evolution of head and lateral lanterns luciferases in Phengodidae remains unknown. In the present work, we cloned by PCR the cDNA for lateral lantern luciferases of three Mastinocerini species: Phrixothrix hirtus, Brasilocerus sp(3). and Taximastioncerus sp. The results suggest that the head and lateral lanterns luciferases in Mastinocerini are coded by paralogous genes, and that the ancestral luciferase in the Phengodinae subfamily produced green bioluminescence. The evolutionary history of bioluminescence colors within Phengodinae is discussed.